Characterization of Extracts from Winery By-Products with Antifungal Activity Against Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Vivanco-Millares, M; Vivanco-Millares, M (2013)
Phenolic compound profiles of grape pomace extracts from a mixture of Chilean grape varieties (Cabernet Sauvignon, Carmènere and Syrah) were analyzed. Two extraction methods were used: solvent and soxhlet extraction, followed by fractionation with hexane, chloroform and ethyl acetate. Phenolic compounds in different fractions were identified by HPLC. Ethyl acetate phase of solvent extraction contained a wide variety of phenolic compounds. Hexane phase of the extracts presented lowest diversity. Quercetin was found in almost all fractions.Also, the in vitro antifungal activity of these extracts against the phytopathogenic fungus Botrytis cinerea was evaluated. Hexane or chloroform fractions from extracts obtained by solvent extraction showed the highest inhibitory effect on mycelia growth of this fungus, with IC 50 value of 40ppm. In general, ethyl acetate fractions were less active against B. cinerea. Therefore, it can be concluded that grape pomace are a good low cost source to obtain antifungal extracts. © 2012 Elsevier B.V.